Temporary, but Essential Requirement of CD8+ T Cells Early in the Pathogenesis of Diabetes in BB Rats as Revealed by Thymectomy and CD8 Depletion - Herman Groen; Flip Klatter; Jennie Pater; Paul Nieuwenhuis; Jan Rozing (Clinical and Developmental Immunology)
Autoimmunity-prone BB rats demonstrate a T lymphocytopenia and abnormal T cell subset distribution. To test whether the life span of all T cells or only of certain subsets is reduced in BB rats, we thymectomised 8-week-old BB and PVG rats and subsequently assessed size and composition of the T cell population over a 6-week-period. In both strains, thymectomy (Tx) was followed by a decrease in peripheral T cell numbers, which was proportionally larger in BB rats. The decline of the Thy-1+ recent thymic migrant (RTM) T cell phenotype was similar in both strains. BB rats showed a rapid preferential loss of CD8+ and CD45RC+ T cells, whereas the relative loss of RT6+ T cells was proportional to that of all T cells and not significantly different from that in PVG rats. Tx at 8-week did not prevent diabetes. Tx of 4-week-old BB rats revealed essentially the same changes in peripheral T cell subset distribution as in 8-week-old animals. However, Tx at week 4 did prevent diabetes. Since this raised the possibility of a temporary requirement of CD8+ T cells for the development of diabetes, we performed CD8 depletions during different pre-diabetic intervals. We found that CD8 depletion from 4 to 8 and 4 to 14 weeks, but not from 8 to 14 weeks of age prevented diabetes. We conclude that the protective effect of early adult Tx is, at least in part, due to the rapid loss of CD8+ T cells, and that these cells are only required between 4 and 8 weeks of age for diabetes to develop in BB rats.